Fiscal Adjustment in IMF-Supported Programs. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2003)
Using a cross-country sample of 169 IMF-supported programs and detailed studies of 15 programs, this evaluation report examines various aspects of fiscal adjustment in IMF-supported programs. It presents evidence that does not support some critics' view that IMF-supported programs typically adopt a one-size-fits-all approach to fiscal adjustment, nor the perception that programs always involve austerity by targeting reductions in public spending. The report also proposes a number of recommendations for IMF surveillance and program design in the future.